(untitled) (Journal of the College of Basic Education, 2022)
The research aims to present the tools of communication and communication in virtual societies and explain their characteristics and their relationship to media activities and information science. Digital identity between enrichment and concealment, and the emergence of types of identity, the most prominent of which are two types, one of which clings to the real identity and declares the real data, and the other in which the individual is hidden and anonymous and a common framework of protocols and technical standards in participation, "Digital Citizenship"